GK_Gmat wrote:

Upstream:

D = 90 m

S= (v-3) m/hr

Let T = t

Downstream:

D=90

S=(v+3) m/hr [let this be statement 1]

T = t-1/2 = (2t-1)/2 [let this be statement 2]

D=ST

Since D is the same upstream & downstream:

=> t(v-3) = (v+3)(2t-1)/2

=> 2tv-6t = 2tv+6t-v-3

=> v+3=12t or t=(v+3)/12 [let this be statement 3]

Using the value of t from statement 3 in statement 2 we get T=(V-3)/12

D= S * T

=> 90= (v+3)(v-3)/12

=>v^2=1089

=>v=33 [let this be statement 4]

Therefore, when going downstream:

D= 90

S = v+3 = 33+3 = 36 m/hr

T = 90/36 = 2.5 hrs.

Not sure if the above is correct. Even if it is, I'm sure there's a much simpler way to solve this.

Your approach is perfect and answer is absolutely correct. But what "I" or "we" need is a fast approach to be able to solve it within 2 minutes!

Anyone with some fast approach?